Availability of distance education requirements at the Algerian University- Analytical study of the opinions of a sample of university professors - HAMDI, Mohammed Yacine; KHENNICHE, Youcef (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2023)
This study aims to find out the availability of the requirements of the distance education system, on which Algerian universities relied as an auxiliary system for traditional education, during and after the Corona virus crisis that swept the world, from the point of view of a sample of university professors. The descriptive approach was relied on in the theoretical side, and the questionnaire tool was used for collecting and processing data in the applied side of the study. The results of the study concluded that the human requirements are met on average in the distance education process, while there is a significant weakness in the technical and administrative requirements, according to the opinions of 30 professors from various Algerian universities. As for the appropriate human requirements for distance education, we concluded that most professors are proficient in various electronic programs, and have the ability to combine traditional education with distance education. With regard to the knowledge and skills of technical staff, we concluded that they were unable to provide the necessary support for the distance education process, and with regard to the appropriate technical requirements for distance education, it was noted that most professors did not create an electronic version of the standards they teach, in addition to the fact that most of them still have ambiguity about the effectiveness of distance education platforms. Also, with regard to equipment and software, we concluded that there is no periodic maintenance of the hardware, and the lack of design of auxiliary software on the method of distance education, and finally regarding the administrative requirements of the distance education system, we noticed that no amendments were made to the criteria for student success, as well as the lack of periodic evaluations of the distance education system, and no instructions were given on how to deal with the attendance and absence of students from lessons and lectures. This may be due to the lack of legal texts that amend the criteria for success, and the calculation of student absences.